2023
DOI: 10.1017/s1368980023001994
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric nutritional status of children (0–18 years) in South Africa 1997–2022: a systematic review and meta-analysis

Herculina Salome Kruger,
Marina Visser,
Linda Malan
et al.

Abstract: Objective: To conduct a comprehensive systematic review and meta-analysis of the available literature on the anthropometric nutritional status of South African infants and children, 0–18 years old and to report on trends of changes in nutritional status over the period 1997–2022. Design: Systematic review and meta-analysis. Setting: Review of the available literature on the anthropometric nutritional status of South African infants and children, 0–18 years old, over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 86 publications
(177 reference statements)
0
0
0
1
Order By: Relevance
“…The observed prevalence (7.5%) of stunting among adolescents in this study was lower than the prevalence of stunting that we recently reported among adolescents in north Sudan (19.8%) [23]; among schoolchildren aged 5-15 years in eastern Sudan (22.1%) [20]; among school-age children in Ebonyi State in Nigeria (9.9%) [19]; among street adolescents in the city of Adama, Oromia Region, Ethiopia (34.1%) [10], and Tanzania (18%) [14]; and among 7625 adolescents from 8 countries in sub-Saharan Africa (18.1%) [15]. Moreover, our results revealed a lower prevalence of stunting compared with the pooled prevalence of stunting reported in a meta-analysis among adolescents in South Africa (9•6%) [6] and Ethiopia (22.4%) [7]. On the other hand, the prevalence (7.5%) of stunting in our study was higher than that recently reported (5.7%) among school adolescents in high schools in the town of Durame in Ethiopia [11].…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations
“…The observed prevalence (7.5%) of stunting among adolescents in this study was lower than the prevalence of stunting that we recently reported among adolescents in north Sudan (19.8%) [23]; among schoolchildren aged 5-15 years in eastern Sudan (22.1%) [20]; among school-age children in Ebonyi State in Nigeria (9.9%) [19]; among street adolescents in the city of Adama, Oromia Region, Ethiopia (34.1%) [10], and Tanzania (18%) [14]; and among 7625 adolescents from 8 countries in sub-Saharan Africa (18.1%) [15]. Moreover, our results revealed a lower prevalence of stunting compared with the pooled prevalence of stunting reported in a meta-analysis among adolescents in South Africa (9•6%) [6] and Ethiopia (22.4%) [7]. On the other hand, the prevalence (7.5%) of stunting in our study was higher than that recently reported (5.7%) among school adolescents in high schools in the town of Durame in Ethiopia [11].…”
Section: Discussioncontrasting
confidence: 50%
“…A recent report revealed the increasing burden of both underweight and obesity among children and adolescents worldwide, particularly in low- and middle-income countries [ 5 ]. Moreover, the double burden of malnutrition (stunting and overweight/obesity) is widely prevalent among adolescents in Africa [ 6 ]. Several studies have been published on the prevalence of nutritional status and its associated factors among adolescents in sub-Saharan Africa [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pemantauan status gizi yang dilakukan secara berkala dan terjadwal akan memberikan gambaran status gizi sehingga dapat dilakukan tindakan pencegahan masalah gizi pada anak usia sekolah dasar. Menurut Kruger et al, (2023) bahwa status gizi optimal pada anak usia sekolah akan mendukung perkembangan fisik dan mental sehingga akan berdampak pada perkembangan ekonomi.…”
Section: Pendahuluanunclassified